Quantification and Characterisation of Microplastics in Organic Waste-Derived Soil Amendments - Alessandro Rimmaudo; Alan Cundill; Ian Singleton; Donald Morrison; Aimeric Blaud (Water, Air, & Soil Pollution, 2026)
The spread of organic waste-derived amendments such as compost, anaerobic digestate and biosolids has been identified as a major source of microplastics in agricultural soil, with potential negative environmental and human health effects. Due to lacking regulatory frameworks and standard monitoring procedures, the extent of microplastic contamination in Scottish organic waste-derived soil amendments is still poorly understood. This study investigated the presence, quantity and characteristics (morphology, density and colour) of microplastics in anaerobically digested biosolids, green-waste-derived compost and food-waste-derived anaerobic digestate produced in Scotland. Microplastics (100—5000 µm) were present in all analysed samples in concentrations ranging from 34 to 160 particles g −1 dw, with the highest levels found in biosolids, followed by digestate and compost. High-density fibres represented 55.8—66.4% of microplastics in biosolids, likely polyester from the domestic washing of textiles. In addition to microplastics, > 20,000 cellulosic microfibres g −1 dw, likely textile-derived natural fibres, were detected in biosolids, and were absent in other samples. Microplastic fibres of a wider-density-range represented 72% of microplastic in compost, while high-density microplastic fragments (34%) and fibres (24%) were the most abundant microplastics in digestate. Based on the results, it was estimated that compost, anaerobic digestates and biosolids could respectively introduce 3.17 × 10 12 , 5.9 × 10 11 and 7.2 × 10 12 microplastic particles measuring 100—5000 μm to Scottish land, annually. These findings highlight the extent of microplastic contamination in terrestrial environments across Scotland, underscoring the need for standardised routine monitoring, enhanced waste management practices, and stricter regulatory measures.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Reconstructing the demographic history of orang‐utans using Approximate B ayesian Computation - Alexander Nater; Maja P. Greminger; Natasha Arora; Carel P. van Schaik; Benoit Goossens; Ian Singleton; Ernst J. Verschoor; Kristin S. Warren; Michael Krützen (Molecular Ecology, 2015)
Investigating how different evolutionary forces have shaped patterns of DNA variation within and among species requires detailed knowledge of their demographic history. O rang‐utans, whose distribution is currently restricted to the S outh‐ E ast A sian islands of B orneo ( P ongo pygmaeus ) and S umatra ( P ongo abelii ), have likely experienced a complex demographic history, influenced by recurrent changes in climate and sea levels, volcanic activities and anthropogenic pressures. Using the most extensive sample set of wild orang‐utans to date, we employed an Approximate B ayesian Computation ( ABC ) approach to test the fit of 12 different demographic scenarios to the observed patterns of variation in autosomal, X ‐chromosomal, mitochondrial and Y ‐chromosomal markers. In the best‐fitting model, Sumatran orang‐utans exhibit a deep split of populations north and south of L ake T oba, probably caused by multiple eruptions of the T oba volcano. In addition, we found signals for a strong decline in all S umatran populations ~24 ka, probably associated with hunting by human colonizers. In contrast, B ornean orang‐utans experienced a severe bottleneck ~135 ka, followed by a population expansion and substructuring starting ~82 ka, which we link to an expansion from a glacial refugium. We showed that orang‐utans went through drastic changes in population size and connectedness, caused by recurrent contraction and expansion of rainforest habitat during Pleistocene glaciations and probably hunting by early humans. Our findings emphasize the fact that important aspects of the evolutionary past of species with complex demographic histories might remain obscured when applying overly simplified models.

Effect of ozone on spore germination, spore production and biomass production in two Aspergillus species - Sanjay Antony-Babu; Ian Singleton (Antonie van Leeuwenhoek, 2009)

Intestinal Parasites of Free-ranging, Semicaptive,and Captive Pongo abelii in Sumatra, Indonesia - Irene F. Mul; Wardy Paembonan; Ian Singleton; Serge A. Wich; Hester G. van Bolhuis (International Journal of Primatology, 2007)

Orangutan Home Range Size and Its Determinants in a Sumatran Swamp Forest - Ian Singleton; Carel P. van Schaik (International Journal of Primatology, 2001)